Application of Digital Technologies for Internal Audit : A Bibliometric Literature Review - Yadav, Tanya; Kulkarni, Prasanna; Chirputkar, Abhijit (Indian Journal of Finance, 2025)
Purpose : Digitization has impacted every facet of life, and there has been a notable surge in the usage of digital technologies in internal auditing. The study provided a detailed summary and intellectual foundation of digital technologies in the internal audit research field. Methodology : To do network mapping with a single study, this research combined network analysis and bibliometrics and included 215 papers published between 1989 and 2024. Findings : The research showed that most studies on the transition to digital technologies in internal audit have been conducted in the UK, USA, Malaysia, and Indonesia. Furthermore, the examination revealed important theoretical foundations, novel methods, and future lines of inquiry. The trajectory of contemporary research in internal auditing is toward digital technologies. Practical Implications : Advanced technologies make it possible to do routine tasks, gain deeper insights from massive amounts of data, and conduct more effective and higher-quality internal audits. Traditionally, the audit procedure involved manually gathering and organizing vast amounts of data by hand. Today, audit procedures are changed by artificial intelligence (AI), machine learning (ML), and advanced analytics. Internal auditors can compare and examine conflicting data sets using predetermined criteria. Originality : This research appears to be one of the few studies that use bibliometric analysis to investigate theoretical research on the application and adoption of digital technologies in internal auditing.